(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Abstract: Bacteria are pathogenic germs that cause a variety of diseases in humans, ranging from minor to life-threatening. Proper detection of the disease-causing bacterial agent is required for proper treatment of patients affected with these disorders. Bacteria are classified into two groups: Gram Positive Bacteria and Gram Negative Bacteria. Both types of bacteria have a variety of inherited biochemical traits that allow us to distinguish them, check for their presence and absence, and determine whether they are gram negative or gram positive. As a result, the current review focuses on describing many biochemical assays in a single piece. Conclusion Gram positive bacteria are identified using biochemical tests such as the catalase test, coagulase test, starch hydrolysis test, and nitrate test, while Gram negative bacteria are identified using biochemical tests such as the oxidase test, urease test, indole test, sulfur test, and methyl red /voges-proskauer test. The analytical profile index test 20E was created to distinguish between Gram-negative Enterbacteriacea and non-Enterbactriacea bacteria. Gram-positive microbes such as Staphylococcus species, Micrococcus species, and other related organisms have also been generated using the API method.